Preliminary trophic flow models of two west African lagoons. - LALEYE, PHILIPPE A.; Villanueva, M.C; Laë, R; Albaret, J; De Moraïs, Tito; Simier, M; MOREAU, Jeacques (My University, 2007)
An attempt was macle to const,ruct trophic models of two West African coastallagoons u sing the Ecopat b approach. The lagoons Nokoué (Benin) and Ebrié (Ivory Coast) are considered in this study to compare trophic stru cture and dynam ics. Results observed are discussed to improve our understanding of the ecological functioning of such ecosystems. Fur cher assessment on fluxes ofbiomass and consequential ecological behaviour from this holistic approach will hclp develop gu idel ines for optimum management of these ecosystems
Keywords: Lagoons; Ecopath; trophic dynamics; Lake Nokou é; Ébrié Lagoon; Benin